Argonaute binding within 3′-untranslated regions poorly predicts gene repression. Issue 13 (5th June 2020) - Chu, Yongjun; Kilikevicius, Audrius; Liu, Jing; Johnson, Krystal C; Yokota, Shinnichi; Corey, David R
Abstract: Despite two decades of study, the full scope of RNAi in mammalian cells has remained obscure. Here we combine: (i) Knockout of argonaute ( AGO ) variants; (ii) RNA sequencing analysis of gene expression changes and (iii) Enhanced Crosslinking Immunoprecipitation Sequencing (eCLIP-seq) using anti-AGO2 antibody to identify potential microRNA (miRNA) binding sites. We find that knocking out AGO1, AGO2 and AGO3 together are necessary to achieve full impact on steady state levels of mRNA. eCLIP-seq located AGO2 protein associations within 3′-untranslated regions. The standard mechanism of miRNA action would suggest that these associations should repress gene expression. Contrary to this expectation, associations between AGO and RNA are poorly correlated with gene repression in wild-type versus knockout cells. Many clusters are associated with increased steady state levels of mRNA in wild-type versus knock out cells, including the strongest cluster within the MYC 3′-UTR. Our results suggest that assumptions about miRNA action should be re-examined.